Assessing the challenging factors towards green initiatives in Indian electronic industries: a framework and evaluation. (3rd May 2019) - Mathiyazhagan, K.; Sehrawat, Shivani; Sharma, Bhumika; Elangovan, K.
Globally industries are under pressure to incorporate environmental consideration in traditional activities based on demand from customers and government regulations. But industries are facing a lot of problems in analysing and identifying the influential challenging factors for adopting eco-friendly and green practices in traditional activities. This paper reviews the scenario of green supply chain management (GSCM) in India as well as the electronics industry perspective based on extensive literature review. Also, this study focuses on identifying the most influential challenging factors for adoption of green initiatives in traditional practices with the help of decision making trial and evaluation laboratory (DEMATEL) approach. A total of 35 challenging factors were identified based on literature and discussion with industry experts, then 20 challenging factors were considered for further analysis. This study involved 30 electronics SMEs in and around the Delhi - National Capital Region (NCR) of India, and more than 15 academicians were also consulted.